Pengembangan Sterilisator Alat Pelindung Diri (APD) Bagi Tenaga Medis Pasien Covid-19 Berbasis IoT - Supardiyono Supardiyono; Pudjijuniarto Pudjijuniarto (Indonesian Journal of Engineering and Technology (INAJET), 2021)
To avoid the bad possibility of contracting Covid-19, the PPE used by medical personnel must be sterile. Sterilization is carried out to remove all microorganisms attached to PPE when handling Covid-19 patients. The specific purpose of this research is to design and build a personal protective equipment (PPE) sterilizer for Covid-19 patients by combining 3 technologies, namely UV sterilization, ozonation, and heater. The methods used to build personal protective equipment (PPE) sterilizers for medical staff for Covid-19 patients are as follows: 1) Formulating problems related to PPE for medical personnel for Covid-19 patients in hospitals, 2) Determining the method, namely designing PPE sterilizers consisting of: stages: preparation, design, manufacture, assembly, function testing and implementation, 3) adding UV, ozone and heating sterilizers as sterilization units 4) developing chamber units and racks/trays that can be knocked down and designed for automatic models, 5) control PPE sterilization time and temperature control system. Based on the research that has been done, it can be said as follows: 1) All components of the PPE Sterilization Tool work well, 2) The UV lamp used in this tool is a 30W Philips T8 UV lamp with a radiation value of 100 W/cm2, the highest lamp efficiency value at a lamp temperature of 400 C with 100% efficiency., 3) A suitable temperature for sterilization with a UV lamp is in the range from 400 to 800 C, 4) When sterilization is based on a “Dry Heat” temperature, the optimum is in the range of 600 – 800 C.